A minimal change disease (MCD) related nephrotic syndrome preceding a Hodgkin Lymphoma diagnosis - A case report - Pedro Almiro e Castro; Nuno Afonso Oliveira; Rui Alves (Publicações Ciência e Vida, 2022)
We admitted a 21 -year -old female to the Nephrology ward due to proteinuria and generalized oedema, which started soon after consuming clonixin 300mg thrice a day for two weeks. Her initial blood work showed nephrotic -range proteinuria, hypoalbuminaemia, hypercholesterolaemia and normal kidney function. We conducted a full auto -immune and serological study: there were no signs of infection, complement consumption or underlying auto -immune diseases. Suspecting minimal change disease, we started prednisolone 1mg/kg/day, with good clinical response and a reduction of urinary protein losses. By the third day, a kidney biopsy was performed: the glomeruli were morphologically normal and no immune deposits were found, which suggested minimal change disease. After seven days, the patient was discharged from the hospital with a corticoid taper until her Nephrology consultation. In the following weeks she maintained clinical and laboratorial remission and prednisolone was stopped after six months. Two months after, the patient noticed a growing bilateral cervical mass and went to the emergency room. The diagnostic workup was inconclusive, so an ultrasound -guided biopsy was requested. The biopsy revealed lymphoid cell proliferation, positive for CD30, CD15, MUM -1 and BCl6. These findings confirmed a Hodgkin's Lymphoma diagnosis and the patient started radiotherapy and chemotherapy (ABVD -doxorubicin, bleomycin, vinblastin, dacarbazine). In the following months her clinical status improved and the cervical mass had a significant size reduction. The kidney disease remained in remission, without therapeutic adjustments. A post- -treatment PET scan was requested, showing only a residual mediastinal mass.